2009
DOI: 10.1111/j.1751-1097.2009.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared Photoinactivation of Bacteria and Fungi at Physiologic Temperatures

Abstract: We examined a laser system (870 and 930 nm), employing wavelengths that have exhibited cellular photodamage properties in optical traps. In vitro, with 1.5 cm diameter flat-top projections (power density of 5.66 W cm(-2)), at physiologic temperatures, we achieved photoinactivation of Staphylococcus aureus, Escherichia coli, Candida albicans and Trichophyton rubrum. Using nonlethal dosimetry, we measured a decrease in trans-membrane potentials (DeltaPsimt and DeltaPsip) and an increase in reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 60 publications
0
62
0
4
Order By: Relevance
“…The generation of reactive oxygen species (ROS), resulting from the absorption of laser radiation at the mitochondrial level, has been proposed as a major molecular mechanism underlying the photoinactivating action of laser therapy on microbial species, including C. albicans and Staphylococcus [9]. Indeed, increased ROS generation might be responsible for the induction of apoptosis observed in our experiments.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The generation of reactive oxygen species (ROS), resulting from the absorption of laser radiation at the mitochondrial level, has been proposed as a major molecular mechanism underlying the photoinactivating action of laser therapy on microbial species, including C. albicans and Staphylococcus [9]. Indeed, increased ROS generation might be responsible for the induction of apoptosis observed in our experiments.…”
Section: Discussionmentioning
confidence: 68%
“…In these studies, treatments have been performed by using a wide range of sources, differing in power (class I-III lasers, with power lower than 0.5 W, and class IV lasers, with power higher than 0.5 W), wavelength [mostly in the red and nearinfrared (NIR) bands], and emission (single and combined, continuous and pulsed mode). Although some studies reported an increase in the mortality of C. albicans in vitro [7][8][9], the molecular and cellular mechanisms underlying the effects of laser therapy on microorganisms and host tissues remain largely unknown. Recently, the effects of two treatment protocols differing in wavelength (λ 635 nm versus λ 970 nm) and energy density (0.375 J/cm 2 versus 375 J/cm 2 ) have been studied and compared in an animal model of chemotherapyinduced OM.…”
Section: Introductionmentioning
confidence: 99%
“…Bornstein i wsp. [31] wykazali ich skuteczność in vitro i in vivo w stosunku do C. albicans i T. rubrum, w temperaturze fizjologicznej, niepowodującej uszkodzenia tkanek gospodarza. Szersze badania kliniczne z wykorzystaniem lasera wytwarzającego fale o długościach 870 nm i 930 nm opublikowali Landsman i wsp.…”
Section: Promieniowanie Laserowe W Leczeniu Grzybicy Paznokciunclassified
“…Na możliwości rozwoju zastosowania terapii fotodynamicznej w leczeniu grzybicy paznokci wskazują również ostatnie publikacje dotyczące poszukiwania nowych, lepszych substancji o działaniu fotouczulającym przeznaczonych do terapii grzybicy paznokci [31].…”
Section: Wykorzystanie Terapii Fotodynamicznejunclassified
“…87 It has been shown that near-infrared light can cause selective photodamage of multidrug-resistant pathogens. 88 In a recent study, it has been demonstrated that photodamage of multidrug-resistant Gram-positive and Gram-negative bacteria by near-infrared (870 nm/930 nm) light potentiates erythromycin, tetracycline and ciprofloxacin. 89 Although the antibiotics used in this study are MES substrates and therefore it is reasonable to assume that near infrared light may play role in efflux inhibition the experimental evidence is rather weak and this possibility requires further exploration.…”
Section: Ps Delivery and Nanomedicinementioning
confidence: 99%